An ATP-fueled nucleic acid signal amplification strategy for highly sensitive microRNA detection. Issue 77 (12th September 2018) - Wen, Zhi-Bin; Liang, Wen-Bin; Zhuo, Ying; Xiong, Cheng-Yi; Zheng, Ying-Ning; Yuan, Ruo; Chai, Ya-Qin
Abstract : Herein, an adenosine triphosphate (ATP)-fueled nucleic acid signal amplification strategy based on toehold-mediated strand displacement (TMSD) and fluorescence resonance energy transfer (FRET) was proposed for highly sensitive detection of microRNA-21. Abstract : Herein, an adenosine triphosphate (ATP)-fueled nucleic acid signal amplification strategy based on toehold-mediated strand displacement (TMSD) and fluorescence resonance energy transfer (FRET) was proposed for highly sensitive detection of microRNA-21. More importantly, the target microRNA-21 could be regenerated with ATP as the fuel rather than a nucleotide segment in conventional approaches, which made the proposed strategy simple and efficient due to the high affinity and strength of the aptamer–target interaction.